Processing technology for tempered glass - MAO ZHIQUN (2015)
The invention discloses a processing technology for tempered glass, and belongs to the field of tempered glass. The processing technology comprises the following steps: preheating, rapidly heating, cooling, recooling and naturally cooling. Through preheating before heating, and an intermittent aeration mode at the cooling stage, the toughening degree is accurately controlled, so that the spontaneous explosion phenomenon in the tempered glass processing process is greatly reduced; the yield is improved; and the production cost is reduced.